From quarks to black holes : progress in understanding the logic of nature : proceedings of the International School of Subnuclear Physics - Zichichi, Antonino (Subnuclear series, 2005)
This volume is a unique report on the frontiers of subnuclear physics presented by global specialists in a clear and rigorous style. The question of Lattice QCD is presented by R D Kenway, and that of Quark-Gluon Plasma Physics by F Karsch. Quantum Field theory is discussed by R G Dijkgraff, and the status of Local Supersymmetry by M J Duff. Detailed analysis of Supersymmetry in Nuclei is made by F Iachello, and that of Inflation, Dark Matter and Dark Energy by E W Kolb. Compactified dimensions are outlined by I Antoniadis, Horizons in the quantization of the gravitational force by Nobel Laure.